Hospital accreditation: lessons from low- and middle-income countries - Smits, Helen (BioMed Central, 2014)
The growth of accreditation programs in low- and middle-income countries (LMICs) provides important examples of innovations in leadership, governance and mission which could be adopted in developed countries. While these accreditation programs in LMICs follow the basic structure and process of accreditation systems in the developed world, with written standards and an evaluation by independent surveyors, they differ in important ways. Their focus is primarily on improving overall care country-wide while supporting the weakest facilities. In the developed world accreditation efforts tend to focus on identifying the best institutions as those are typically the only ones who can meet stringent and difficult evaluative criteria. The Joint Learning Network for Universal Health Coverage (JLN), is an initiative launched in 2010 that enables policymakers aiming for UHC to learn from each other’s successes and failures. The JLN is primarily comprised of countries in the midst of implementing complex health financing reforms that involve an independent purchasing agency that buys care from a mix of public and private providers [Lancet 380: 933-943, 2012]. One of the concerns for participating countries has been how to preserve or improve quality during rapid expansion in coverage. Accreditation is one important mechanism available to countries to preserve or improve quality that is in common use in many LMICs today. This paper describes the results of a meeting of the JLN countries held in Bangkok in April of 2013, at which the current state of accreditation programs was discussed. During that meeting, a number of innovative approaches to accreditation in LMICs were identified, many of which, if adopted more broadly, might enhance health care quality and patient safety in the developed world. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12992-014-0065-9) contains supplementary material, which is available to authorized users.